Shyness dan Peer Attachment: Faktor Risiko atau Pelindung terhadap Problematic Internet Use pada Remaja? - Cynthia Alinda Putri; Dyan Evita Santi; Aliffia Ananta (JIWA: Jurnal Psikologi Indonesia, 2025)
Abstract Adolescents are in a developmental stage where relationships with peers become the primary source of emotional support, social identity, and self-regulation. When attachment to peers is not fulfilled, characterized by poor communication, lack of trust, and feeling alienated from peers, it causes adolescents with poor peer attachment to tend to be isolated from their peers. Thus, shyness, or the condition of feeling uncomfortable in interactions and being prone to restlessness, makes adolescents withdraw from their environment. These two conditions encourage adolescents to seek comfort through the online world, which can trigger excessive and maladaptive internet use, commonly known as Problematic Internet Use. This reserach adopts a quantitative approach employing multiple linear regression analysis. The data were collected through a random cluster sampling method, involving a sample of 365 students from 2 (two) State Junior High Schools in Ponorogo, with sample age criteria of 13-15 years using a questionnaire that measures peer attachment, shyness, and problematic internet use. The findings of multiple linear regression analysis indicate that the significance values of peer attachment (X1) and shyness (X2) on problematic internet use (Y) are 0.000 (p < 0.01), which indicates a highly significant relationship between the two independent variables and problematic internet use. This means that together, peer attachment and shyness can be very significant predictors of problematic internet use Keywords: Adolescent; Peer Attachment; Problematic Internet Use; Shyness Abstrak Remaja berada pada tahap perkembangan di mana hubungan dengan teman sebaya menjadi sumber utama dukungan emosional, identitas sosial, dan regulasi diri. Ketika kelekatan dengan teman sebayanya tidak terpenuhi yang ditandai dengan buruknya komunikasi, kurangnya kepercayaan, dan merasa terasing dengan teman sebayanya menyebabkan remaja dengan tingkat kelekatan teman sebaya yang buruk cenderung terasingkan dari teman sebayanya sehingga malu atau disebut shyness merupakan kondisi individu merasa tidak nyaman dalam berinteraksi, cenderung gelisah yang membuat remaja menarik diri dari lingkungannya. Kedua kondisi ini mendorong remaja untuk mencari kenyamanan melalui dunia maya yang dapat memicu penggunaan internet secara berlebihan dan maladaptif, biasa diketahui sebagai Problematic Internet Use. Penelitian ini menggunakan metode kuantitatif dengan teknik analisis regresi linear berganda. Data pada penelitian ini dikumpulkan dengan teknik random cluster sampling dengan jumlah sampel sebanyak 365 siswa pada 2 (dua) Sekolah Mengengah Pertama Negeri di Ponorogo, dengan kriteria usia sampel 13-15 tahun menggunakan kuisioner yang mengukur peer attachment, shyness, dan problematic internet use. Dari hasil analisis regresi linear berganda diketahui bahwa nilai signifikansi peer attachment (X1) dan shyness (X2) terhadap problematic internet use (Y) sebesar 0,000 (p < 0,01), yang mengindikasikan adanya hubungan sangat signifikan antara kedua variabel bebas tersebut dengan problematic internet use, artinya secara bersama-sama peer attachment dan shyness dapat menjadi prediktor yang sangat signifikan untuk problematic internet use. Kata kunci: Adolescent; Peer Attachment; Problematic Internet Use; Shyness